The Synergistic Effect Of Acethonilic Ipomoea cairica Leaf Extract Combined With Entomopathogenic Fungi Metarhizium anisopliae On The Larvae Of Dengue Vectors - Rodzay, Rohaiyu Md (2018)
The common approach to ward-off epidemics of this dengue viruses is depends on chemical insecticides. However, due to the public concerned and environmental protection strategies, more researches on biological control of the vector are actively proposed. The use of bio-potency natural products from plant derivatives, which are Ipomoea cairica (coastal morning glory) and entomopathogenic fungi (Metarhizium anisopliae) were evaluated in this study towards the larvae stage of Aedes aegypti and Aedes albopictus mosquitoes. Ipomoea cairica leaves plant extracts were segregated for the extraction preparation using a Soxhlet apparatus with acetone as the solvent.